Comparing the Effectiveness of Pre-Marriage Training Based on Halford’s Couple Relationship Education and Adlerian Premarital Approach on the Schema Modes of Girls and Boys Applying for Marriage - Tatary , Neda; Mirmehdi, Seyyed Reza; Zanganeh Motlagh, Firouzeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to compare the effectiveness of pre-marriage training based on Halford’s Couple Relationship Education and the Adlerian premarital approach on the schema modes of girls and boys applying for marriage.Materials and Methods: This quasi-experimental research used a multi-group pretest-posttest design with a control group and a three-month follow-up phase. The statistical population consisted of girls and boys applying for marriage who had referred to counseling centers in the city of Darreh Shahr, Ilam. A total of 45 individuals were selected through convenience sampling and randomly assigned to two experimental groups and one control group (15 individuals per group). The data collection tool was the Schema Mode Questionnaire (Young, 2007). Pre-marriage training was provided to the experimental groups weekly, based on Halford’s Couple Relationship Education approach and the Adlerian premarital approach. Data analysis was performed using repeated measures ANOVA and Bonferroni post hoc test at a significance level of 0.05.Findings: The findings indicated that pre-marriage training based on the Adlerian approach had a significant effect on reducing schema modes (p = 0.010). However, the effectiveness of Halford’s Couple Relationship Education on schema modes was not significant (p = 0.356). Additionally, no significant statistical difference was found between the scores of schema modes in the Halford’s Couple Relationship Education group and the Adlerian pre-marriage training group, indicating that both approaches had a similar effect on the schema modes of girls and boys applying for marriage in the posttest and follow-up stages.Conclusion: Based on these results, there is no significant difference in the effectiveness of pre-marriage training based on Halford’s Couple Relationship Education and the Adlerian premarital approach on schema modes.